ANALYSIS OF THE CHARACTERISTICS OF CREATIVE WORKS IN UZBEKISTAN LITERATURE OF THE 20TH-21ST CENTURIES (International Conference on Education, Psychology and Humanities, 2026)
In this article, we will get acquainted with the works of artists who created in the genre of tuyuk in the 20th-21st centuries. The poetic features of their tuyuks will be analyzed. The use of metaphors, the meanings conveyed by tuyuks, and the goals of the artists behind their tuyuks will be highlighted.
Keywords: Tuyuk, rhythm, fingering, rhyme.